Peran Gender dalam Hubungan Seks pada Wanita Hamil - Budi Asty Andini; Khobibah Khobibah; Mimi Ruspita (Jurnal Kebidanan dan Kesehatan Tradisional, 2020)
Background: Sexual intercourse during pregnancy is a physiological need for pregnant women that is influenced by factors of perception from within oneself and previous experience and gender role factors in the family with the aim of knowing the relationship between gender roles and sexual relations in pregnant women. Methods: Non-experimental research with a population of all pregnant women in the village of Curugsewu in the District of Patean. The total sample of pregnant women receiving antenatal care was 30 with the Kendal statistical test. Results: significance T = 0.022 <0.005 there is a relationship between gender roles and sexual relations of sufficient strength in the negative direction -391*.Conclusion: there is a relationship between gender roles and sexual relations, the husband's role is very dominant but the frequency of sex in early pregnancy is largely not done because it is influenced by cultural factors and a history of previous abortion sex.